The pearl rush in Aru, 1916; A case study in writing commodity history in Southeast Asia - Vickers, Adrian (Wacana, Journal of the Humanities of Indonesia, 2019)
While the long history of “commerce” in Southeast Asia is well studied, less examination has been made of the histories of capitalism, particularly in terms of the encounters that took place around commodities. This article provides a translation and analysis of a description of Dobo on Aru in 1911. At the time it was a “Klondike”, on what Julia Martínez and I have termed “the pearl frontier”. The Aru islands were the site for an Australian-led pearl shell consortium that ran from the beginning of the twentieth century until the 1940s, which brought in a large number of Japanese divers and other Asian and Pacific workers. Examining relations around the pearling industry provides a number of general methodological points of entry into the ways that commodity relations created encounters with modernity.